Phenazine-Producing Rhizobacteria Promote Plant Growth and Reduce Redox and Osmotic Stress in Wheat Seedlings Under Saline Conditions - Yuan, Peiguo; Pan, Huiqiao; Boak, Emily N.; Pierson, Leland S.; Pierson, Elizabeth A. (Frontiers in Plant Science, 2020)
Application of plant growth-promoting bacteria can induce plant salt stress tolerance, however, the underpinning microbial and plant mechanisms remain poorly understood. In the present study, the specific role of phenazines produced by rhizosphere-colonizing Pseudomonas in mediating the inhibitory effects of salinity on wheat seed germination and seedling growth in different varieties was investigated using Pseudomonas chlororaphis 30-84 (wild type) and isogenic derivatives deficient or enhanced in phenazine production. The results showed that varieties differed in how they responded to the salt stress treatment and the benefits derived from colonization by P. chlororaphis 30-84. In all varieties, the salt stress treatment significantly reduced seed germination, and in seedlings, reduced relative water content, increased ROS levels in leaves, and in three of four varieties, reduced shoot and root production compared to the no salt stress treatment. However, inoculation of seeds with Pseudomonas chlororaphis 30-84 wild type or derivatives promoted salt-stress tolerance in seedlings of the four commercial winter wheat varieties tested, but the salt-stress tolerance phenotype was not entirely due to phenazine production. For example, all P. chlororaphis derivatives (including the phenazine-producing mutant) significantly improved relative water content in two varieties, Iba and CV1, for which the salt stress treatment had a large impact. Phenazine production also enhanced the shoot or root growth of seedlings of all varieties under non-saline conditions and importantly, all P. chlororaphis derivatives enabled the salt inhibited wheat varieties studied to maintain above ground productivity in saline conditions. Notably, ROS accumulation was reduced, and antioxidant enzyme (catalase) activity enhanced in the leaves of seedlings grown in saline conditions that were seed-treated with the phenazine-producing P. chlororaphis derivatives as compared to non-inoculated seedlings. The results demonstrate the capacity of P. chlororaphis to mediate salt tolerance in wheat seedlings by promoting plant growth and reducing osmotic stress and a role for phenazine production in reducing redox stress.